Effects of Velocity on Work Production about the Human Elbow Joint During Stretch-Shortening and Non-Stretch-Shortening Tasks - Benoit, Daniel (My University, 1997)
The performance enhancement of stretch shortening cycle (SSe) contractions has been well documented in the literature. However, the majority of these studies have been performed either on gross human systems for multijointed movements, or in isolated animal muscle studies using in-vitro preparations. This study was designed to apply the principles used for these invitro animal studies to the human system, under conditions that would allow results to be directly associated with a specific muscle or muscle group. Previous investigations by Lynch (1992) and Benoit and Dowling (1995) have supported the use of muscle models to predict elbow flexor torque and sse performance enhancement. The purpose of this study was to use an EMG based muscle model to investigate the possible relationship between sse tasks at different frequencies of elbow flexion-extension and performance enhancement of the elbow flexor muscles.
A Hill based muscle model was used to predict elbow flexor torque of seven healthy male subjects (23-40 years of age) under voluntary and stimulated contraction conditions. EMG of the elbow flexors and extensors was recorded from the biceps brachii and triceps respectively. Elbow flexor stimulation was done transcutaneously with a voltage equivalent to a 60% MVe torque; stimulation lasted four seconds at a frequency of 50 Hz. A simulated constant muscle activation torque was also derived from the muscle model for all trials. Externally measured torque was measured using a strain gauge located on a shaft situated along the axis of rotation of the elbow joint. A torque motor was used to drive the forearm (fastened to a manipulandum) at four frequencies of elbow flexion-extension (.58, 1.5, 2.4, and 3.3 Hz) over a range of 162 to 105 degrees of elbow extension. Non-SSe trials were performed at these same velocities and over the same range of motion. Torque was then integrated as a function of joint angle displacement to yield the work produced about the elbow. Passive work was subtracted from all trials.
The results indicate that a significant increase in muscle work followed sse tasks as opposed to non-SSe tasks and this increased work was relatively highest at 2.4 Hz. Work about the elbow decreased with increasing frequency of movement for both sse and non-sse conditions. The simulated constant activation muscle model predicted work well for all trials and conditions, indicating muscle model accuracy. The EMG driven model predicted well for all non-SSe trials but significantly underestimated the work for sse tasks, suggesting a decrease in myoelectric activity. This decrease was evidenced by a decrease in average M-wave amplitude with increasing SSe velocity. This study indicates that the contractile component is directly involved in optimizing muscle work during sse tasks and that the performance enhancement of sse tasks may take place at the myofilament and cross-bridge level.
Keywords: Velocity; Work Production; Human Elbow; Joint; Stretch-Shortening; Non-Stretch-Shortening